2016
DOI: 10.1002/jmri.25230
|View full text |Cite
|
Sign up to set email alerts
|

Modified triexponential analysis of intravoxel incoherent motion for brain perfusion and diffusion

Abstract: Background To noninvasively obtain more detailed information on brain perfusion and diffusion using modified triexponential analysis. Methods On a 3.0 Tesla MRI, diffusion‐weighted imaging of the brain with multiple b‐values was performed in healthy volunteers (n = 12). We derived perfusion‐related, fast‐free, and slow‐restricted diffusion coefficients (Dp, Df, and Ds, respectively) and fractions (Fp, Ff, and Fs, respectively) in the frontal and occipital white matter, caudate nucleus, and putamen calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 0 publications
2
31
1
Order By: Relevance
“…14,23,24 Recent work 22 has shown that both the pseudo-diffusion and FW compartments should be considered when including the non-weighted image in the model fitting. This suggests the need for at least three compartments for an accurate disentanglement of partial volume effects in the brain, which is in line with other studies on brain 25 and non-brain [26][27][28] tissue. However, the appropriate fit of multiple exponentials with non-linear leastsquares (NLLS) approaches is a difficult and time-consuming numerical problem.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…14,23,24 Recent work 22 has shown that both the pseudo-diffusion and FW compartments should be considered when including the non-weighted image in the model fitting. This suggests the need for at least three compartments for an accurate disentanglement of partial volume effects in the brain, which is in line with other studies on brain 25 and non-brain [26][27][28] tissue. However, the appropriate fit of multiple exponentials with non-linear leastsquares (NLLS) approaches is a difficult and time-consuming numerical problem.…”
Section: Introductionsupporting
confidence: 84%
“…26,27,58 Furthermore, the diffusion coefficients of the three observed components were in agreement with previously reported literature values of brain tissue, FW and blood pseudo-diffusion. 3,8,25 Recent studies have suggested the existence of multiple components in the pseudo-diffusion part itself (i.e. micro-and macrovascular network).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision for fitting a triexponential model was made because of recent reports indicating that a triexponential model might be more appropriate. 11,12,[17][18][19] The formula for the biexponential IVIM model reads 20 :…”
Section: Methodsmentioning
confidence: 99%
“…We would like to thank the authors of the letter for their interest and comments on our recent article. 1 They have questioned our fitting procedure in which the fast-free diffusion coefficient (D f ) was fixed to the diffusion coefficient of free water at 378C (3.0 3 10 23 mm 2 /s). Moreover, they have interpreted that the fast and slow diffusion component fractions (F f and F s , respectively) correspond to the extracellular and intracellular water fractions, respectively, based on the results of previous studies [2][3][4][5] and showed that their fractions depended on whether the diffusion analysis was performed with constrained or unconstrained fits.…”
mentioning
confidence: 99%